The effectiveness of interventions used to improve general health check uptake by the older adult population: a systematic review and meta-analysis. - Wing Yan Lau; Jinxiao Lian; Maurice Yap (PLOS Global Public Health)
Undergoing general health check enable early detection of common diseases and giving individuals a sense of control over their wellbeing. However, the general health check uptakes are typically unsatisfactory. Various interventions have been introduced to improve general health check uptakes. This review aims to answer how well these interventions work. A comprehensive literature search was conducted in four electronic databases in August 2020 and updated between 2021 and 2024. Randomised controlled trials (RCTs) that met the inclusion criteria were selected. Meta-analysis was performed on qualified RCTs to estimate the overall effectiveness of the interventions. The components of intervention were characterised using the Behaviour Change Technique Taxonomy. A total of 3360 records were screened. Eight RCTs were finally included. Among these RCTs, nine types of interventions were identified with all implemented in the invitation stage, including enhanced invitation letters, telephone invitations, question-behaviour-effect (QBE) questionnaires, financial incentives, leaflets, pre-notification short message service (SMS), SMS reminders, reminder letters and point-of-care automated prompts to clinical staff. All these interventions showed a significant improvement in the general health check uptakes than the control groups, except leaflets and QBE questionnaires. A total of fifteen behaviour change techniques were used in these interventions. A meta-analysis showed the pooled effect of these interventions was significantly associated with the improvement in the general health check uptakes than the control (OR =1.30, 95% CI =1.15 - 1.46). However, the high heterogeneity observed (84%) could reduce the reliability of the pooled summary effect. This review found that interventions primarily implemented during the invitation process are effective in improving the general health check uptake rates. Future research should aim to extend these interventions beyond the invitation stage to address internal and external barriers that deter older adults from seeking general health checks. The systematic review protocol is registered on PROSPERO (ref: CRD42021221041).